Selection of potential Bacillus starters for cocoa beans fermentation improvement - Wilfried YAO (Annals of the University Dunarea de Jos of Galati. Fascicle VI: Food Technology, 2017)
Bacillus sp. strains isolated from six main Ivorian cocoa producer regions were investigated based on their biochemical properties in order to select the best one as potential starter. Three mains technological and useful properties for good cocoa beans fermentation were monitored for 970 isolated Bacillus sp. strains. Thus, 44.54% pectinolytic Bacillus sp. strains revealed by clear halo diameter in plate assay were confirmed by enzymes production (pectinase and polygalacturonase) in liquid medium. Moreover, 51.10% of these strains displayed both the ability to acidify the medium and to degrade the citrate. Among these pectinolytic enzymes producing strains previously selected, ten were able to maintain this activity in conditions of varying pH and temperature as same as fermentation heap with an activity ranged within 0.20±0.02- 0.51±0.05µmol/min/mg of proteins for polygalacturonase (PG) and 0.22±0.04- 0.76±0.06µmol/min/mg of proteins for pectinase. Four of them (T9G4, T11I10, T3D23 and T4A44) selected as the best based on pectinase production level were identified as Bacillus thuringiensis. These strains were able to continuously produce both pectinolytic enzymes in different conditions of organic components: acids (acetic and lactic) influence with 0.2% as limit of tolerance, citric acid influence (up to 1% of tolerance) and ethanol influence higher than 8%. The technological properties of the four best strains highlighted in this study may make them suitable candidates as starter for cocoa fermentation control.